Recovery of platinum(IV) and palladium(II) from complex hydrochloric acid matrices by a thiodiglycolamide derivative - Paiva, A. P. (2014)
The solvent extraction performance of N,N’-dimethyl-N,N’-dicyclohexylthiodiglycolamide (DMDCHTDGA) towards Pt(IV) and Pd(II) in HCl solutions has recently been published. It was shown that these two platinum-group metals (PGMs) are efficiently extracted from 8 M HCl aqueous phases, being subsequently separated by sequential strippings: 1 M HCl allows Pt(IV) recovery, whereas Pd(II) is only back-extracted by thiourea in HCl. In this work, selectivity tests were carried out to evaluate the performance of DMDCHTDGA towards the recovery of both PGMs, from 8 M HCl aqueous phases, when in presence of Rh(III), Fe(III), Ni(II), Zn(II), Al(III), Ce(III) and Zr(IV), simulating the leaching solutions that may result from the hydrometallurgical treatment of spent automobile catalytic converters. It was generally observed that the additional metal ions do not affect the recovery of Pd(II) and Pt(IV) by DMDCHTDGA. Fe(III), Zn(II) and Zr(IV) are co-extracted with Pt(IV) and Pd(II); Fe(III) and Zn(II) were efficiently scrubbed with water, whereas Zr(IV) was removed by an acidified aqueous solution. Inversely, Ni(II) is not extracted, and Rh(III) and Ce(III) appear only traceably in the loaded organic phase. Al(III) is a concern, as it is appreciably extracted, and none of the tested backextraction solutions was able to strip it.